Chaotic sequence based polar code encrypted scheme in negative secrecy capacity case - Xiaohui ZHANG; Shunliang ZHANG; Bowen LI (Tongxin xuebao)
A chaos based encrypted polar coding scheme,which could be applied to the negative secrecy capacity case,was proposed.Chaotic sequences were employed to encrypt the information bits and fill the frozen bits.And multi-block polar coding structure was also employed in the proposed scheme.The proposed scheme was featured as lower complexity and higher secrecy transmission rate.Corresponding mathematical analysis had been performed in terms of the error probability,security and transmission rate.The result reveals that the proposed scheme can achieve reliability,security in negative secrecy capacity case.What’s more,it has relatively low complexity and high secrecy transmission rate compared with the existing schemes.